Realism and determinism: some thoughts on neoclassical economics - Hodge, Duncan (University of the Free State, 2001)
Neoclassical economics is often criticised for being deterministic and disconnected from social reality. A related criticism is that neoclassical economic theory is instrumentalist. This article argues that neoclassical economics, if properly understood, can be given a realist interpretation. The origins of classical and neoclassical economics are briefly discussed and the scholarly shift away from political economy is located in the marginal utility revolution in economic thought in the 1870s. It is argued that the core assumptions of neoclassical economics capture essential aspects of social reality and are not merely convenient, fictitious abstractions; that the charge of instrumentalism is not entirely justified, and that neoclassical economic theory does not imply that social processes are deterministic or mechanistic in reality.

Neoklassieke ekonomie word dikwels gekritiseer omdat dit deterministies en derhalwe verwyderd van die sosiale werklikheid is. Kritiek wat hiermee verband hou is dat neoklassieke ekonomiese teorie instrumentalisties is. Die oorsprong van klassieke en neoklassieke ekonomie word kortliks bespreek. Die wetenskaplike wending weg van politieke ekonomie hang saam met die omwenteling wat die grensnutbegrip in die 1870s in die ekonomiese denkwyse teweeggebring het. Daar word aangevoer dat die kernaannames van moderne neoklassieke ekonomie wesenlike aspekte van die sosiale werklikheid verreken en nie bloot gerieflike, fiktiewe abstraksies is nie; dat die beskuldiging van instrumentalisme nie heeltemal geregverdig is nie, en dat neoklassieke ekonomiese teorie nie impliseer dat sosiale prosesse in werklikheid deterministies of meganisties is nie.
Keywords: Neoclassical economics; Social sciences; Classic economics; Meaning of realism; Natural sciences